The evolving social context for planning in Australia - Davies, Amanda (Routledge, 2015)
Australia's population, at just over 23 million people, is growing. The population is projected to grow to at least 36 million people by 2061. Moreover, it is anticipated that the population will be based largely within the existing large cities and metropolitan areas. To accommodate this projected population growth there will be a need to increase housing density and develop improved infrastructure and services. In planning for this population growth it is important to consider that a considerable proportion of the population growth will be generated through immigration, and with this will come particular settlement patterns and demands for housing, infrastructure and services. It is also critical to keep in mind the implications of the ageing of Australia's population for the built environment.